2018
DOI: 10.31344/ijhhs.v3i1.65
|View full text |Cite
|
Sign up to set email alerts
|

Tapering Healthcare Budget is a red alert for LMIC countries:The example from Bangladesh

Abstract: not availableInternational Journal of Human and Health Sciences Vol. 03 No. 01 January’19. Page : 5-9

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…This report also confirmed that there is a lack of research to focus on the role of government to oversee and support the private health sector. Islam et al (2018) described that despite having a good infrastructure of health sector both in rural and urban areas but the resources were not used properly in Bangladesh. Even the monetary issue was not the constraint, whereas allocating small amount in managerial and operational logistic expenses could improve the scenario dramatically.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This report also confirmed that there is a lack of research to focus on the role of government to oversee and support the private health sector. Islam et al (2018) described that despite having a good infrastructure of health sector both in rural and urban areas but the resources were not used properly in Bangladesh. Even the monetary issue was not the constraint, whereas allocating small amount in managerial and operational logistic expenses could improve the scenario dramatically.…”
Section: Discussionmentioning
confidence: 99%
“…Though public spending on health is central to universal health coverage, the country spends less on health care than other countries in South Asia and less than most countries in the world (Islam et al , 2018). Therefore, the authors are motivated to explore that how Bangladesh has achieved the noteworthy success in health-care sector with this low budgetary allocation.…”
Section: Introductionmentioning
confidence: 99%